Conceptualisation of Social Justice Model as an Advanced Framework of Inclusive Education Tracing the Trajectory - Datta, Geetika (JOURNAL OF INDIAN EDUCATION, 2021)
Inclusion is based on the ideology that all children belong together and therefore, educational systems must respond to the diverse needs of all learners and ensure participation of all students in their learning. The systems not only should be responding, but acknowledging, accepting and celebrating diversity of all kinds so that every individual of the group feels accepted, safe and empowered. Traditionally, the theoretical framework of inclusion is derived from the field of Special Education wherein, the paradigms have shifted from the flawed Medical model to the Social model. This paper tries to conceptualise Social Justice Model as an advanced theoretical framework of Inclusion. It traces the trajectory of policies and social processes, prejudices and dysconsciousness prevailing in Indian society, specifically pertaining to CWSN and Transgender persons. Thereafter, an attempt has been made to elaborate on the rationale and dimensions of Social Justice as an apt model for Inclusive Education.